2013
DOI: 10.18553/jmcp.2013.19.9.799
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Impact on a U.S. Health Plan Adopting Abiraterone Acetate Plus Prednisone for the Treatment of Patients with Metastatic Castration-Resistant Prostate Cancer

Abstract: BACKGROUND: Abiraterone acetate, an androgen biosynthesis inhibitor, received FDA approval in 2011 for metastatic castration-resistant prostate cancer (mCRPC) patients who have received prior chemotherapy containing docetaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 21 publications
1
31
0
2
Order By: Relevance
“…For ten of the models of chronic illness, the clinical data indicated that a decrease in mortality or disease progression rates during the model time horizon would be expected with use of the new drug [47][48][49][50][51][52][53][54][55][56]. Eight of these models used a simple cost-calculator model structure [47][48][49][50][51][52][53][54], and only two used a decision-analytic model structure [55,56].…”
Section: Decreased Mortality or Disease Progression Ratesmentioning
confidence: 99%
See 4 more Smart Citations
“…For ten of the models of chronic illness, the clinical data indicated that a decrease in mortality or disease progression rates during the model time horizon would be expected with use of the new drug [47][48][49][50][51][52][53][54][55][56]. Eight of these models used a simple cost-calculator model structure [47][48][49][50][51][52][53][54], and only two used a decision-analytic model structure [55,56].…”
Section: Decreased Mortality or Disease Progression Ratesmentioning
confidence: 99%
“…Eight of these models used a simple cost-calculator model structure [47][48][49][50][51][52][53][54], and only two used a decision-analytic model structure [55,56]. Seven of the eight cost-calculator models were for advanced or metastatic cancers [47-51, 53, 54], and one was for congestive heart failure [52].…”
Section: Decreased Mortality or Disease Progression Ratesmentioning
confidence: 99%
See 3 more Smart Citations